Meta-Analyses of Manganese Superoxide Dismutase Activity, Gene Ala-9Val Polymorphism, and the Risk of Schizophrenia. Issue 36 (September 2015) - Wang, Dong-Fang; Cao, Bing; Xu, Mei-Yan; Liu, Ya-Qiong; Yan, Lai-Lai; Liu, Rong; Wang, Jing-Yu; Lu, Qing-Bin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Schizophrenia is a complex and disabling psychiatric disorder, and tardive dyskinesia (TD) is a severe adverse drug effect occurring in 20% to 40% of schizophrenic patients chronically treated with typical neuroleptics. Previous studies suggested that the manganese superoxide dismutase (MnSOD) activity was associated with the development of schizophrenia. Ala-9Val polymorphism, a functional polymorphism of MnSOD gene, has been reported to be related to the risk of schizophrenia and TD. However, these studies did not lead to consistent results. We performed meta-analyses aiming to assess the association between MnSOD activity and schizophrenia, as well as the association of MnSOD Ala-9Val polymorphism with schizophrenia and TD in schizophrenic patients. We search for the literature on MnSOD and schizophrenia in English or Chinese published up to May 1, 2015 on PubMed, EMBASE, the Cochrane Databases, Chinese National Knowledge Infrastructure, China Biology Medical and Wanfang databases. Two investigators independently reviewed retrieved literature and evaluated eligibility. Discrepancy was resolved by consensus with a third reviewer. Data were pooled using fixed-effect or random-effect models. The standardized mean difference (SMD) and 95% confidence interval (CI) were calculated for the MnSOD activity. Pooled odds ratio (OR) and 95% CI were calculated for Ala-9Val genotype and allele frequencies. There were 6, 6, and 10 studies entering 3 parts of meta-analyses, respectively. The MnSOD activity of patients was significantly lower than that of controls (SMD = −0.94; 95% CI: −1.76, −0.12; P  = 0.025). No significant associations of Ala-9Val genotypes (OR = 1.14; 95% CI: 0.97, 1.33; P  = 0.109) and alleles (OR = 1.06; 95% CI: 0.94, 1.20; P  = 0.361) with the risk of schizophrenia were observed. We also did not reveal significant associations of the genotypes (OR = 0.82; 95% CI: 0.66, 1.02; P  = 0.075) and alleles (OR = 0.90; 95% CI: 0.76, 1.06; P  = 0.215) with the risk of TD in schizophrenia. The decreased MnSOD activity may be associated with the risk of chronic schizophrenia in Chinese population, while MnSOD Ala-9Val polymorphism may not play a significant role in the development of schizophrenia and TD. Longitudinal studies with larger sample sizes and different ethnicities are needed to confirm the association of the MnSOD Ala-9Val variants with schizophrenia and TD.